1992
DOI: 10.1016/0885-3924(92)90118-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of survival of patients admitted to a Palliative Care Unit: A prospective study

Abstract: In a prospective open study, 61 consecutive patients with advanced cancer admitted to a Palliative Care Unit underwent survival estimation by two independent physicians after a complete medical exam performed during the first day of admission. An independent research nurse also assessed each patient during the first day of admission. The assessment included activity, pain, nausea, depression, anxiety, anorexia, dry mouth, dyspnea, dysphagia, weight loss, and cognitive status. After the assessment was completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(128 citation statements)
references
References 7 publications
8
115
0
5
Order By: Relevance
“…The strong but time-dependent association of low KPS with survival may explain in part why previous work either did not support the prognostic role of performance status in terminal cancer patients 53 or have found performance status independently associated with survival only in patients with shorter life expectancies. 54 The presence or severity of certain symptoms, such as weakness, dyspnea, and anorexia, may help to identify the patients for whom performance status assessments have greater prognostic value.…”
Section: Discussionmentioning
confidence: 93%
“…The strong but time-dependent association of low KPS with survival may explain in part why previous work either did not support the prognostic role of performance status in terminal cancer patients 53 or have found performance status independently associated with survival only in patients with shorter life expectancies. 54 The presence or severity of certain symptoms, such as weakness, dyspnea, and anorexia, may help to identify the patients for whom performance status assessments have greater prognostic value.…”
Section: Discussionmentioning
confidence: 93%
“…3,10,34 These studies have been limited, however, by their focus on inpatients, by their exclusion of patients with diagnoses other than cancer, or by their incomplete or short follow-up or small or nonrepresentative samples. Moreover, previous studies of survival among patients in hospices either have neglected the role of diagnosis 33 or have not found a relation between diagnosis and the length of survival after enrollment 34 ; some studies, however, have suggested a relation between certain diagnoses and the timing of patients' referral to hospices. 29,35 The duration of survival after enrollment in a hospice is an important outcome to measure because it is relevant to the quality and cost of care that patients receive at the end of life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of single hospices, both in the United States and abroad, have found median survival times of 11 to 30 days, [26][27][28][29][30][31][32][33] and those based on data from multiple hospices have found survival times of 25 to 35 days. 3,10,34 These studies have been limited, however, by their focus on inpatients, by their exclusion of patients with diagnoses other than cancer, or by their incomplete or short follow-up or small or nonrepresentative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen articles were identified which examined the prognostic indicators of survival. They are listed in table 3 ( 7, 1 0, 1 1 , 16,[18][19][20][25][26][27][28][29][30][31][32][33][34][35].…”
Section: 16-24)mentioning
confidence: 99%